Immersive Virtual Reality for Clinical Pain: Considerations for Effective Therapy - Donegan, Tony; Ryan, Brenda E.; Swidrak, Justyna; Sanchez-Vives, Maria V. (Frontiers in Virtual Reality, 2020)
Immersive virtual reality is transforming medical and psychological research and treatment, including the treatment of clinical pain. In this short perspective paper, we present some of the methodological difficulties that are rarely discussed in the literature of pain research when using virtual reality. These often-unmentioned problems can confound research investigations or interfere with the therapeutic efficacy in clinical trials. We propose practical solutions based on our research experience. We first outline the mechanisms of, and challenges to, the sensations of embodiment and presence, which are critical to creating effective virtual reality illusions, before discussing the particular considerations that need to be contemplated when working with patients with clinical pain. Finally, we discuss some upcoming technological advances that may influence significantly this rapidly expanding field in the near future.